Self-regulated Learning Plan in Mathematics 5 (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Self-regulated learning (SLR) is recognized as an important predictor of learner academic motivation and achievement. This process requires learners to independently plan, monitor, and assess their learning to become master of their own learning. However, only a few learners naturally do this well. This research aimed to test the effectiveness of self–regulated learning activities as a basis for Mathematics 5 Learning Material. The respondents were all 13 learners enrolled in fifth grade at Lower Wallayan Elementary School, a small, public elementary school in Wallayan, Bagulin, La Union. This study made use of a quasi-experimental design, one group pretest-posttest design. During the fourth quarter of the school year, learners were taught methods of learning Mathematics 5 through the self-regulated learning material. The materials necessary to carry out the intervention consists of activities for learners to regulate their learning. The scores were recorded before and after the implementation of the self-regulated learning intervention. A t-test was used to compare the mathematics scores. It was found that there is a significant difference between the level of learners' competence in Mathematics before and after the intervention, which shows that the self-regulated learning activities are effective on the mathematics competency level of learners as a basis for a Mathematics 5 Learning Material. Therefore, teachers of various areas such as mathematics gain awareness of self-regulated learning strategies in the first place, understand their importance, and use them. Thus, the Self-regulated Learning Material was validated and is recommended for its adoption.
Keywords: Self –regulated learning activities, Mathematics competencies, motivation